2017
DOI: 10.4038/cmj.v62i1.8432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary artery disease in a semi urban population in Southern Sri Lanka

Abstract: Introduction Prevalence of coronary artery disease (CAD) is on the rise in Sri Lanka resulting in high hospital mortality rates. Because of paucity of community based data on CAD we carried out this study to assess prevalence of CAD and associated factors in a suburban population in Southern Sri Lanka.Methods A cross sectional descriptive study was carried out among community living adults aged 30 years or more in Bope-Poddala Medical Officer of Health (MOH) area. Total of 1000 eligible individuals were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In Sri Lanka life expectancy for females is higher than males. Also over the last few decades, life expectancy for both genders is progressively going up [ 80 , 81 ]. Scientific studies carried out on CAD are limited in the Sri Lankan literature [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Sri Lanka life expectancy for females is higher than males. Also over the last few decades, life expectancy for both genders is progressively going up [ 80 , 81 ]. Scientific studies carried out on CAD are limited in the Sri Lankan literature [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…12 The incidence of IHD in Sri Lanka has increased considerably over the past two decades. 13 Further, recent studies have revealed a growing increase in IHD among the younger generation in Sri Lanka and its risk factors are concentrated among urban populations and those in the higher socioeconomic classes. 14 Moreover, IHD was the leading cause of hospital death in the country during the past 10 years, accounting for nearly 10% of all hospital deaths.…”
Section: Development Of a Counseling Intervention Protocol To Improve...mentioning
confidence: 99%
“…14 Moreover, IHD was the leading cause of hospital death in the country during the past 10 years, accounting for nearly 10% of all hospital deaths. 15 However, western countries report a considerably low death rate due to technically advanced interventional procedures, 16 which are very expensive 13 for lower-income countries like Sri Lanka. Therefore, this study suggests a socioculturally applicable cost-effective health counseling intervention for improving adherence to physical activity, diet, and medication in patients with IHD in Sri Lanka.…”
Section: Development Of a Counseling Intervention Protocol To Improve...mentioning
confidence: 99%
“…Hospital statistics in Sri Lanka indicated a rapid rise in morbidity and mortality due to CVD during the past 2 decades [3], and this would cause a significant impact on quality of life of individuals and country's economic growth. There is no national level estimate of prevalence of CVD, however, a prevalence of 6.9% in adults aged 30 years and above was reported in a sub-urban area [4]. The 10-year CVD risk is a measure of an individual's risk based on a combination of risk factors, and the proportion at high risk has been reported in the Sri Lanka non-communicable disease risk factor survey (STEPS 2015) and in a cohort study [5,6].…”
Section: Introductionmentioning
confidence: 99%